ANTIOXIDANT AND ANTIBACTERIAL PROPERTIES OF ZIZIPHUS MUCRONATA AND RICINUS COMMUNIS LEAVES EXTRACTS - Nemudzivhadi, Vhutshilo; Masoko, Peter (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Plants have always been a successful source of remedy from nature. With the widespread use of medicinal plants by indigenous people, the search for biologically active agents is relevant as these plants have the potential to provide pharmacologically active compounds. This study aimed for investigating the effect of antioxidant and antibacterial properties of Ziziphus mucronata Willd (Rhamnaceae) and Ricinus communis L. (Euphorbiaceae). Materials and methods: Antibacterial activity was evaluated using microdilution assay and bioautography. Antioxidant activities were determined by using 2, 2-diphenyl-1-picrylhydrazyl (DPPH). In vitro cytotoxicity was determined using the tetrazolium-based colorimetric assay. Results: R. communis leaves had eight secondary metabolites. Quantitative assay for R. communis, chloroform and methanol extracts had very high antioxidant activity compared to vitamin C. Plants extracts from all solvents exhibited high antibacterial activity against Staphylococcus aureus, Enterococcus faecalis, Escherichia coli and Pseudomonas aeruginosa with minimum inhibitory concentration (MIC) values between 0.21 and 1.05 mg/ml. Most of the antibacterial compounds observed on bioautography had Rf values ranging from 0.21 to 0.88. Z. mucronata had LC50 of 105.5 μg/ml and R. communis 131.8 μg/ml on Vero cells. Conclusion: This study revealed that both plants had free radical scavenging and antibacterial activities.